Genetic variants in nucleotide excision repair pathway predict survival of esophageal squamous cell cancer patients receiving platinum‐based chemotherapy. Issue 11 (12th August 2018) - Zhang, Ruoxin; Zhou, Fei; Cheng, Lei; Yu, Alexandria; Zhu, Meiling; Wang, Mengyun; Zhang, Zhuanxu; Xiang, Jiaqing; Wei, Qingyi
Abstract : The benefits of platinum‐based chemotherapy (PBC) on survival of esophageal squamous cell carcinoma (ESCC) patients are inexplicit due to the varied therapeutic effects. Nucleotide excision repair (NER) pathway plays a vital role in removing platinum‐DNA adducts in tumor cells and hence may modulate the therapeutic effect and survival outcome. The present study assessed the associations of 26 potentially functional regulatory single nucleotide polymorphisms (rSNPs) in nine core NER genes with disease‐free survival (DFS) and overall survival (OS) in 339 ESCC patients. We found that ERCC2 rs2097215 T and rs3916788 A, ERCC5 rs3759497 A and XPC rs3731054 C alleles were associated with unfavorable DFS. Patients carrying high‐risk allele group (HRG, 5‐8 risk alleles) had a significantly shorter DFS, compared with those carrying low‐risk alleles (LRG, 0‐4 risk alleles) [adjusted hazards ratio (HRadj ) = 1.64, 95%CI = 1.23‐2.19, P adj  < 0.001]. Three of these SNPs (ie, ERCC2 rs2097215 T and rs3916788 A and ERCC5 rs3759497 A) were also significantly associated with a poorer OS (HRG vs LRG: HRadj  = 1.75, 95%CI = 1.23‐2.47, P adj  = 0.002). The expression quantitative trait loci (eQTL) analysis revealed significant genotype‐expression correlations for ERCC5 rs3759497 and ERCC2 2097215 and rs3916788, which suggest regulatory roles of these SNPs. It appears that these NER variants may independently or jointly exert an impact on survival outcome of Chinese ESCC patients undergoing adjuvant platinum‐based therapy. Large studies are warranted to validate these findings.